(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Bibliometry coupling is used to process bibliographic data to assert existing latent information on publication material. We apply here this technique on patent data gathered from the OPS web service to enhance the exploration process of patents using network visualization. The following will present briefly graph theory preliminaries, the gathering and transforming process on the ops base. The different networks produced will be discussed and placed in a generic economic intelligence process. Finally we present a case study using this approach to discuss the democratization of 3D printing. Palavras-chave: Industrialization. Revolution. Innovation. Production. Technology. Link para o texto completo (PDF) https://periodicos.ufsc.br/index.php/eb/article/view/1518-2924.2014v19n40p117